Juridical Analysis of Using the Panel Body Suspension Strategy and Jurisprudence in "Similar Matter" Trade Dispute Settlement at the WTO (Case Studies DS593 and DS600) - Arief Budiyanto (Journal Research of Social Science, Economics, and Management, 2025)
The handling of WTO disputes DS593 (Indonesia vs. the European Union) and DS600 (Malaysia vs. the European Union) concerning the EU’s Renewable Energy Directive II (RED II) demonstrates the strategic use of Dispute Settlement Understanding (DSU) procedures in managing institutional risk and ensuring jurisprudential coherence amid the Appellate Body impasse. Both disputes focused on allegations of de facto discrimination in the treatment of palm oil-based biofuels under TBT Article 2.1 and GATT Article III:4. The appointment of identical Panelists under DSU Article 9.3 ensured consistency in findings—acknowledging the legitimacy of the EU’s environmental objectives under GATT Articles XX(b) and XX(g), while concluding that their implementation failed the procedural fairness standards of the GATT Article XX chapeau due to arbitrary administration. Moreover, Indonesia’s use of DSU Article 12.12 to delay the DS593 Panel report until after DS600’s publication illustrates the tactical use of procedural rights to maximize political and legal leverage. These findings highlight both the procedural sophistication of developing countries in WTO litigation and the ongoing tension between environmental legitimacy and equitable trade governance.